1997
DOI: 10.2527/1997.7571715x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of timing of gain on growth and reproductive performance of beef replacement heifers.

Abstract: Our objective was to determine whether beef heifers could be developed by delaying the majority of weight gain until the last third of the developmental period before the onset of the breeding season. Spring-born Angus x Hereford heifers were used in each of two consecutive years and were allotted at weaning to gain either .45 kg/d for the entire developmental period (yr 1 = 159 d, n = 40; yr 2 = 168 d, n = 40; EVENGAIN) or to gain .11 kg/d from d 0 to 112, followed by .91 kg/d from d 112 to 159 (yr 1, n = 40)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 11 publications
4
31
0
5
Order By: Relevance
“…The decreased percentage of EXT heifers being pubertal was likely the result of several factors including growth rate, winter diet, possibly monensin supplementation, which was a function of diet quality, and other behavioral and environmental factors differing in each development system. These data agree with recent literature indicating reduced postweaning ADG resulting from lower diet quality, with or without moderate realimentation before breeding, reduces the percentage of heifers attaining puberty (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995Buskirk et al, , 1996Marston et al, 1995;Lynch et al, 1997;Ciccioli et al, 2005;Gasser et al, 2006). Martin et al (2008) indicated reducing the percentage of mature BW at breeding by approximately 6% resulted in a nonsignificant, 17% decrease in percentage of pubertal heifers at breeding.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The decreased percentage of EXT heifers being pubertal was likely the result of several factors including growth rate, winter diet, possibly monensin supplementation, which was a function of diet quality, and other behavioral and environmental factors differing in each development system. These data agree with recent literature indicating reduced postweaning ADG resulting from lower diet quality, with or without moderate realimentation before breeding, reduces the percentage of heifers attaining puberty (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995Buskirk et al, , 1996Marston et al, 1995;Lynch et al, 1997;Ciccioli et al, 2005;Gasser et al, 2006). Martin et al (2008) indicated reducing the percentage of mature BW at breeding by approximately 6% resulted in a nonsignificant, 17% decrease in percentage of pubertal heifers at breeding.…”
Section: Resultssupporting
confidence: 81%
“…Genetics may have adapted to minimize the negative effect of delayed puberty on firstservice conception. Previous research indicates no effect of moderate nutrient restriction leading to reduced ADG during postweaning development, regardless of pubertal effects, on first service conception or percentage of heifers calving to the first conception (Lalman et al, 1993;Buskirk et al, 1995;Lynch et al, 1997;Funston and Deutscher, 2004;Martin et al, 2008). Similarly, in the present study, grazing heifers on CR or winter grass for a portion of postweaning development did not affect (P = 0.23) AI conception rate compared with heifers developed in a DL.…”
Section: Resultsmentioning
confidence: 40%
See 1 more Smart Citation
“…Se podrían utilizar niveles bajos de alimentación durante los primeros meses del periodo de recría y suplementar a los animales para alcanzar un plano alto de alimentación con la antelación suficiente para utilizar la habilidad de los animales de razas cárnicas para aprovechar el crecimiento compensatorio y ganar peso rápida y eficientemente, sin afectar a la respuesta reproductiva (Lynch et al, 1997).…”
Section: Resultados Y Discusiónunclassified
“…Consequently, the availability of seeded and fertilized improved pastures, in most situations, is an important factor for successful management of pregnant beef heifers. Cultivated pastures would then be needed to grow the female calves of approximately 160 kg at weaning to reach to 60-65% of adult weight, close to 260-280 kg head -1 in November at the onset of breeding (Lynch et al 1997). However, cultivated pastures are also frequently used to feed pregnant heifers during winter months.…”
Section: Introductionmentioning
confidence: 99%